EasyFinance: Developing the Capacities for Growth - FU, Xin; Velamuri, S. Ramakrishna (Senate Hall, 2009)
EasyFinance is a Chinese training company founded in 2004, focusing on finance training. It was set up by two trainers, and Marshall Ma joined in 2005, as the third partner. EasyFinance has experienced rapid growth since its inception by doubling its revenues every year and has become the dominant player in the fragmented and highly competitive Chinese finance training market in 2008. The work force has reached 31 and the organizational structure and processes are also well established. Marshall and his two partners expect to keep doubling revenues for another three years. However, EasyFinance is playing in a relatively small market segment and the shortage of qualified trainers is a bottle-neck that his business has to overcome. Marshall and his team need to identify a feasible way to achieve their ambition. The case touches upon 1) the challenge entrepreneurial firms face of achieving sustained growth and 2) organizational development issues in professional service firms, with a special focus on attracting and retaining talent. Keywords: entrepreneurship, China, professional service firms, growth; organizational development, training; start-up.
Keywords: entrepreneurship|China|professional service firms|growth|organizational development|training|start-up